2009
DOI: 10.1177/0363546509343201
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Deficiency Causes Brain Plasticity

Abstract: The current study reveals that anterior cruciate ligament deficiency can cause reorganization of the central nervous system, suggesting that such an injury might be regarded as a neurophysiologic dysfunction, not a simple peripheral musculoskeletal injury. This evidence could explain clinical symptoms that accompany this type of injury and lead to severe dysfunction. Understanding the pattern of brain activation after a peripheral joint injury such as anterior cruciate ligament injury lead to new standards in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
177
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(191 citation statements)
references
References 50 publications
9
177
2
3
Order By: Relevance
“…Similar to a recent report 8 of the same movement task in a cohort of ACL-deficient individuals, the ACL-POST-R knee had increased activation of a visual-spatial area (lingual gyrus), premotor areas, and the secondary somato- sensory cortex. The role of the lingual gyrus in motor control is unclear, but it may be related to visual processing and specifically to encoding images and memory related to motion.…”
Section: Cerebral Activation Differences For the Acl-post-r Kneesupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to a recent report 8 of the same movement task in a cohort of ACL-deficient individuals, the ACL-POST-R knee had increased activation of a visual-spatial area (lingual gyrus), premotor areas, and the secondary somato- sensory cortex. The role of the lingual gyrus in motor control is unclear, but it may be related to visual processing and specifically to encoding images and memory related to motion.…”
Section: Cerebral Activation Differences For the Acl-post-r Kneesupporting
confidence: 84%
“…3 Researchers have reported that these postinjury neurologic differences include disrupted central nervous system afferent function, 4,5 altered efferent output, 3,6 and changes in brain activity for motor control. 7,8 Few investigators have prospectively studied the neurologic changes that occur in the brain after ACL injury, reconstruction, and rehabilitation and before subsequent injury. Therefore, the purpose of this paper was to describe the brain activation for knee motor control measured after initial ACL reconstruction (ACLR) and 3 weeks before a contralateral ACL injury.…”
mentioning
confidence: 99%
“…A growing body of brain activation imaging research has revealed that ACL deficiency can cause reorganization of the central nervous system at both the spinal and supraspinal levels. 15,29 These changes appear to persist following ACLR, 7 potentially manifesting in bilateral postural control impairments.…”
mentioning
confidence: 99%
“…12 It is plausible that both limbs are affected by unilateral trauma, possibly due to physical inactivity after the injury and/or surgery, altered sensory feedback from the injured joint affecting the uninjured side, 28 or modifications to central motor programs, including decreased proprioceptive input-induced plasticity in response to the initial asymmetry. 5,29 Indeed, reports of centrally mediated postural control changes have led to suggestions that ACL injury should be regarded as a neurophysiologic dysfunction and not simply a peripheral musculoskeletal injury. 29 Alternatively, the bilateral balance deficits that we observed may have been present prior to ACL injury, and may have been a contributing factor in the original ACL rupture.…”
mentioning
confidence: 99%
“…Recently a few researchers followed these research line and started exploratory pioneer work to add measures of brain activity in sensorimotor control after ACL injury. They detected brain areas like the frontal and parietal cortical areas related to higher executive functions, somatosensory information processing and the cerebellum due to fine-tuning in sensorimotor control which serve as a neuronal correlate to motor behavior [13][14][15]. It is hypothesized that the working memory as a mechanism for integration of relevant information into the movement planning may play specific a role after ACL injury [13].…”
mentioning
confidence: 99%